Dua Spesies Cacing Soil Transmitted Helminths pada Sayuran Selada (Lactuca sativa) Yang Dijual di Warung Makan pada Kecamatan Seberang Ulu II Palembang - Prameswarie, Thia; Chairil, Ahmad Ghiffari; Prameswari, Meta (Sriwijaya Journal of Medicine, 2019)
Soil-Transmitted Helminths (STH) is a round intestinal worm whose life cycle requires soil. Ascaris lumbricoides, Trichuris trichiura, hookworm sp and the prevalence in Indonesia currently range from 20-86%. Transmission of disease usually food-borne and un-hygienic behaviour. The purpose of this study was to identify the contamination of Soil-Transmitted Helminths (STH) eggs in lettuce (Lactuca sativa). This research has been conducted in Seberang Ulu II Palembang District in 2018. The research method was descriptive cross-sectional with laboratory tests using 0.2% NaOH and then examined under a microscope in June 2018 until January 2019. The sample in this study were 372 lettuce leaves from 31 food stalls, each of the food stalls is taken 12 lettuce leaves. The results were 9 eggs Ascaris lumbricoides (29%), 2 Hookworm sp eggs (6%), but not the Trichuris trichiura eggs. It conclued that there are two species, Ascaris lumbricoides and hookworms sp., of egg worms on lettuce fresh vegetables (Lactuca sativa). The distribution of STH egg positivity is classified as medium in the food stall.